Determinants of antibiotic prescriptions in a large cohort of children discharged from a pediatric emergency department - Covino, Marcello; Buonsenso, Danilo; Gatto, Antonio; Morello, Rosa; Curatole, Antonietta; Simeoni, Benedetta; Franceschi, Francesco; Chiaretti, Antonio (European journal of pediatrics, 2022)
While there is evidence of high use of wide-spectrum antibiotics in children evaluated in the pediatric emergency departments, determinants of this behavior are still unclear. This study was aimed at defining the demographic, social, clinical, and laboratory factors that affect antibiotic prescriptions in children discharged from the emergency department. We performed a retrospective observational study of children aged younger than 18 years discharged from a pediatric university hospital between Jan. 1, 2015 and Dec. 31, 2020. We determined the proportion and type of antibiotic prescription according to demographic, social, clinical, laboratory, and imaging data, as well as doctor’s expertise. Fifty-one thousand six hundred thirty-three children were included, and 13,167 (25.5%) received an antibiotic prescription. Amoxicilline/clavulanate (Am/Cl) was the most prescribed antibiotic (8453, 64.2% of all prescriptions). Factors independently associated with an antibiotic prescription were older age (OR = 1.62 [1.53–1.73] for age 2–5 years, OR = 1.77 [1.64–1.91] for age 6–10 years, OR = 1.36 [1.25–1.49] for age 11–18 years, p < 0.001 for all groups); being evaluated by a physician with > 3 years of pediatric expertise (OR = 1.22 [1.13–1.31], p < 0.001); fever peak higher than 40 °C (OR = 1.37 [1.21–1.54], p < 0.001); abnormal findings on auscultation (OR = 1.95 [1.75–2.17], p < 0.001), CRP values (OR = 1.63 [1.26–2.10] for CRP < 50 mg/L, and OR = 3.78 (2.75–5.21) for CRP ≥ 50 mg/L with respect to CRP not requested; p < 0.01); CXR results whatever positive (OR = 4.47 [3.62–5.52], p < 0.001) or negative (1.82 [1.62–2.04], p < 0.001); being diagnosed with upper respiratory tract infections (OR = 4.27 [4.04–4.51], p < 0.001), lower respiratory tract infections (OR = 5.35 [4.88–5.85]; p < 0.001), and UTI (OR = 9.33 [8.14–10.71], p < 0.001).